Prediction of Optimum Combination of Eudragit RS/Eudragit RL/Ethyl Cellulose Polymeric Free Films Based on Experimental Design for Using as a Coating System for Sustained Release Theophylline Pellets - Abbas Akhgari; Ali Tavakol (Tabriz University of Medical Sciences, 2016)
Purpose: The physicochemical properties of free films made from different mixtures of sustained release polymers were investigated, and an optimum formulation coating on drug containing pellets, based on the study of free film was evaluated. Methods: In order to determine the effect of different variables on the permeability and swelling of films and procedure optimization, the experimental design was fulfilled based on the statistical method of a 33 full factorial design, and according to this method 27 formulations were prepared. The films were prepared using casting-solvent evaporation method. Water vapor permeability, the swelling and permeability of free films in both acidic and buffer media, were carried out. Then, the pellets containing theophylline were coated with the optimum formulation. Results: The results of this study demonstrated that an increase in the free film thickness and Eurdragit RS ratio in films lowered the water vapor transmission (WVT), the swelling and the permeability of all formulations, while an increase in the quantity of ethylcellulose, up to a specific ratio (approximately 40%), decreased the permeability and swelling. The most optimum free film formulation was made up of 60% Eudragit RS and 40% ethylcellulose. Conclusion: Pellets coated with a 10% coating level of ethylcellulose and Eudragit RS (4:6) showed suitable release properties and could serve as a favorable sustained release system for theophylline.